Characterization of red algae (Gracilaria verrucosa) on potential application for topical treatment of oral mucosa wounds in Rattus norvegicus - Hakim, Rachmi F.; Idroes, Rinaldi; Hanafiah, Olivia A.; Ginting, Binawati; Kemala, Pati; Fakhrurrazi, Fakhrurrazi; Putra, Noviandi I.; Shafira, Ghina A.; Romadhoni, Yenni; Destiana, Khaerunisa; Muslem, Muslem (Narra Sains Indonesia, 2023)
Wound healing in the mouth has its challenges due to masticatory movements and the presence of bacteria that can inhibit its process. The aim of this study was to analyze the contents of red algae (Gracilaria verrucosa) from Indonesia, and its potential as a wound-healing agent for oral wounds using animal model. Red algae content was determined by phytochemical tests and gas chromatography-mass spectroscopy (GC-MS). The wound was made by making an incision on the gingival mucosa of Rattus norvegicus and the parameters assessed were bleeding time, number of fibroblast cells, and time of wound closure. Three doses of G. verrucosa gel were used (2.5%, 5%, and 10%) and the gels were applied twice a day, at 6:00 and 18:00. Application was carried out topically by applying 0.1 ml of gel to the incision wound using a 1 mL syringe. Our phytochemical test indicated that the G. verrucosa contained alkaloids, steroids, flavonoids, and phenols. The dominant contains of the G. verrucosa were glycerol (36.81%), hexadecenoic acid (20.74%), and cholesterol (7.4%). The hemostasis test showed that the 2.5% G. verrucosa extract gel had the shortest bleeding time, 33.98±5.33 seconds. On the seventh day of the initial proliferation phase, the number of fibroblasts was not significantly different among groups. On day 14, the number of fibroblasts was only significantly different between 10% G. verrucosa and untreated group (p=0.007). On day 28, however, both 5% and 10% G. verrucosa were significantly higher compared to untreated group, both had p=0.010. Daily clinical examination showed that animals that were given 2.5% and 5% of G. verrucosa extract gel experienced wound closure on day 10. Animals treated with 10% of extract gel, all wounds healed on day 9. This study suggested that G. verrucosa extract could accelerate wound closure and wound healing.